2002
DOI: 10.1128/aac.46.6.1940-1945.2002
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Spectrum Bactericidal Activity of Ag 2 O-Doped Bioactive Glass

Abstract: Bioactive glass has found extensive application as an orthopedic and dental graft material and most recently also as a tissue engineering scaffold. Here we report an initial investigation of the in vitro antibacterial properties of AgBG, a novel bioactive glass composition doped with Ag 2 O. The bacteriostatic and bactericidal properties of this new material and of two other bioactive glass compositions, 45S5 Bioglass and BG, have been studied by using Escherichia coli, Pseudomonas aeruginosa, and Staphylococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
228
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 356 publications
(242 citation statements)
references
References 32 publications
9
228
1
4
Order By: Relevance
“…Localized control of bacteria and inflammation that lead to cellular de-differentiation is needed. The in vitro bioactivity and antibacterial action of a novel sol-gel-derived glass, AgBG, in the system SiO 2 -CaO -P 2 O 5 -Ag 2 O offer a new twenty-first century biomaterials approach towards solving these problems Bellantone et al , 2002Blaker et al 2004;Saravanapavan et al 2004;Lohbauer et al 2005a,b;Jones et al 2006c). The incorporation of 3 wt% Ag 2 O in the bioactive gel glass system confers antimicrobial properties to the glass without compromising its bioactivity.…”
Section: Twenty-first Century Bioceramics Challenge No 4: Control Ofmentioning
confidence: 99%
“…Localized control of bacteria and inflammation that lead to cellular de-differentiation is needed. The in vitro bioactivity and antibacterial action of a novel sol-gel-derived glass, AgBG, in the system SiO 2 -CaO -P 2 O 5 -Ag 2 O offer a new twenty-first century biomaterials approach towards solving these problems Bellantone et al , 2002Blaker et al 2004;Saravanapavan et al 2004;Lohbauer et al 2005a,b;Jones et al 2006c). The incorporation of 3 wt% Ag 2 O in the bioactive gel glass system confers antimicrobial properties to the glass without compromising its bioactivity.…”
Section: Twenty-first Century Bioceramics Challenge No 4: Control Ofmentioning
confidence: 99%
“…Further studies using 45S5 Bioglass ® particles have shown encouraging results regarding potential angiogenic effects of Bioglass ® , i.e., increased secretion of vascular endothelial growth factor (VEGF) and VEGF gene expression in vitro, as well as enhancement of vascularization in vivo [53][54][55][56] (see §4). In addition, the incorporation of particular ions into the silicate network, such as silver [20][21][22] and boron [26,27], has been investigated in order 6 to develop antibacterial and antimicrobial materials. Bioactive glasses can also serve as vehicle for the local delivery of selected ions being able to control specific cell functions [30,[57][58][59][60][61][62][63][64].…”
Section: Figurementioning
confidence: 99%
“…The high amounts of Na 2 O and CaO, as well as the relatively high CaO/P 2 O 5 ratio make the glass surface highly reactive in physiological environments [11]. Other bioactive glass compositions developed over the years contain no sodium or have additional elements incorporated in the silicate network such as fluorine [13], magnesium [14,15], strontium [16][17][18], iron [19], silver [20][21][22][23], boron [24][25][26][27], potassium [28] or zinc [29,30]. Fabrication techniques for bioactive glasses include both traditional melting methods and sol-gel techniques [1, 3,4,10,[31][32][33], the latter are being highlighted elsewhere [34] and are not covered in this review.…”
Section: Introductionmentioning
confidence: 99%
“…5,9 Recently, Ag has attracted attention, and now it is widely used in medical materials owing to its antibacterial effects. 10 Therefore, it was hypothesized that a TiO 2 coating formed on a Titanium silver (TiAg) alloy might exhibit superior antibacterial activity against oral microorganisms to that formed on a Ti substrate alone.…”
Section: Introductionmentioning
confidence: 99%